2011
DOI: 10.1016/j.jcin.2010.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Determinants of Radiation Dose in Percutaneous Coronary Interventional Procedures

Abstract: Several primary determinants of patient radiation dose during PCI were identified. Along with physician development of radiation-sparing methods and skills, pre-procedure dose planning is proposed to help minimize radiation dose for PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
67
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 38 publications
9
67
2
Order By: Relevance
“…Also, when treating complex or CTO lesions, especially in patients with high BMI or previous CABG, radiation management can be incorporated into preprocedure planning as well as in defining maximum levels that could guide physicians in decision making during the procedure accordingly. Finally, we and Fetterly et al 11 have demonstrated that individual PCI operators have a substantial influence on patient dose. Therefore, all staff and trainee physicians should be well trained in behavioral and technical methods to minimize radiation dose.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Also, when treating complex or CTO lesions, especially in patients with high BMI or previous CABG, radiation management can be incorporated into preprocedure planning as well as in defining maximum levels that could guide physicians in decision making during the procedure accordingly. Finally, we and Fetterly et al 11 have demonstrated that individual PCI operators have a substantial influence on patient dose. Therefore, all staff and trainee physicians should be well trained in behavioral and technical methods to minimize radiation dose.…”
Section: Discussionsupporting
confidence: 54%
“…11 Other factors that were associated with increased radiation exposure were body mass index, previous CABG, and peripheral vascular disease. However, in that study, exposure in air values (R, type 1) and the air kerma values (Gy, type 2) were measured and were converted to cumulative skin dose.…”
Section: Discussionmentioning
confidence: 99%
“…17 In fact, technical and anatomic factors during procedures likely have the largest effect on an individual case x-ray exposure. 18,19 As the principal determinant of occupational radiation exposure for operators is patient scatter, reducing total energy to patients directly affects physician and staff exposures as well. 20 Clearly, efforts to reduce radiation exposure for both patient and staff need to be a critical part of every catheterization laboratory's quality improvement mission.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown body mass index to be highly associated with exposure. 18 In addition, chronic total occlusion and bifurcation PCI and number of lesions treated increase exposure. 18,19 With respect to procedure type, endovascular procedures, particularly pelvic and below the, have greater radiation exposure to the operator than coronary procedures.…”
Section: Additional Parameters Affecting Radiation Exposurementioning
confidence: 99%
“…18 In addition, chronic total occlusion and bifurcation PCI and number of lesions treated increase exposure. 18,19 With respect to procedure type, endovascular procedures, particularly pelvic and below the, have greater radiation exposure to the operator than coronary procedures. 20 This is because of the higher dose per frame rate required for digital subtraction and difficulty with shielding.…”
Section: Additional Parameters Affecting Radiation Exposurementioning
confidence: 99%